INFLUENCE OF SHAPE AND SIZE OF PARTICLES ON THE OSSEOINTEGRATION OF POROUS IMPLANTS MADE OF TITANIUM POWDER - M. V. Tumilovich; V. V. Savich; A. I. Shelushina (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The results of studies of the effect of particle size, pore size, shape, metallic-ray powder osteointergatsii quality (germination of bone tissue into the pores of the implant) are given. It is shown that the adhesion strength at the bone tissue implant made from titanium sponge powder 8-11 % higher than that of the implants obtained from spherical powders.